Regulatory Mechanisms and Functional Roles of Hypoxia-Induced Long Non-Coding RNA MTORT1 in Breast Cancer Cells - Cheng, Yi-Chun; Su, Li-Yu; Chen, Li-Han; Lu, Tzu-Pin; Chuang, Eric Y.; Tsai, Mong-Hsun; Chuang, Li-Ling; Lai, Liang-Chuan (Frontiers in Oncology, 2021)
Long non-coding RNAs (lncRNAs) have been found to participate in multiple genetic pathways in cancer. Also, mitochondria-associated lncRNAs have been discovered to modulate mitochondrial function and metabolism. Previously, we identified oxygen-responsive lncRNAs in MCF-7 breast cancer cells under different oxygen concentrations. Among them, a novel mitochondria-encoded lncRNA, mitochondrial oxygen-responsive transcript 1 (MTORT1), was chosen for further investigation. Nuclear, cytoplasmic, and mitochondrial fractionation assays were performed to evaluate the endogenous expression levels of MTORT1 in breast cancer cells. In vitro proliferation and migration assays were conducted to investigate the functions of MTORT1 in breast cancer cells by knockdown of MTORT1. RNA immunoprecipitation and luciferase reporter assays were used to examine the physical binding between MTORT1 and microRNAs. Our results showed that MTORT1 had low endogenous expression levels in breast cancer cells and was mainly located in the mitochondria. Knockdown of MTORT1 enhanced cell proliferation and migration, implying a tumor suppressor role of this novel mitochondrial lncRNA. MTORT1 served as sponge of miR-26a-5p to up-regulate its target genes, CREB1 and STK4. Our findings shed some light on the characterization, function, and regulatory mechanism of the novel hypoxia-induced mitochondrial lncRNA MTORT1, which functions as a microRNA sponge and may inhibit breast cancer progression. These data suggest that MTORT1 may be a candidate for therapeutic targeting of breast cancer progression.